Innate immunity - Honti, Viktor; Kurucz, Éva; Cinege, Gyöngyi; Csordás, Gábor; Andó, István (Acta Biologica Szegediensis, 2015)
In this review, we discuss how studying the Drosophila immune system contributes to a better understanding of the basic principles of innate immunity. We describe the homologies between the insect and the vertebrate immune-regulatory mechanisms and convergent evolutionary traits of the Drosophila and the vertebrate immune system.